G3-4 musculoskeletal discomforts among assembly team members performing assembly welding task - Fazilah, Abdul Aziz; Zakri, Ghazalli; N. M. Zuki, N. M.; Amri, Isfar; N. S. M., Shalahim (Japan Ergonomics Society, 2017)
Work in the automotive assembly plant is physically strenuous and assembly team members are particularly at risk for developing symptoms of musculoskeletal discomforts (MSDs) compared to other sectors. The main aim of this study was to determine the prevalence rate of musculoskeletal discomforts based on the frequency, severity and performance interference among production assembly team members in an automotive component assembly plant. A cross-sectional study was carried out among the production assembly team members who performed manual assembly welding task. The Cornell Musculoskeletal Disorders Questionnaire (CMDQ) data sheets were used in interview with the assembly team members to obtain the prevalence of MSDs. The prevalence of pain in the upper back, lower back, right shoulder and right wrist have been reported to be higher in comparison with pain in other parts of the body. The current study identified the severe musculoskeletal discomfort allies with production assembly line. Assembly team member's lines 4 were reported high mean frequency discomfort, severely discomfort and interfered assembling task performance. It has been discovered; nonetheless, that assembly team member's assembling task performance has interfered with lower back pain. MSD's survey appeared to be very helpful to screen the production assembly team member's health,well-being and performance. The results are also useful for assessing the ergonomics risks factors in the future study.